PEMAHAMAN HUKUM ADMINISTRASI PERTANAHAN BAGI MASYARAKAT DESA SANGLAR KABUPATEN INDRAGIRI HILIR GUNA MENCEGAH KONFLIK DAN SENGKETA PERTANAHAN - Aksar, Aksar; Tua Manik, Saut Maruli; Dinata, Umar (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to analyze the factors that influence the legal understanding of village communities in certifying their land rights to prevent conflicts and land disputes in rural areas. This research is socio-legal research. Socio-legal research is research that combines normative and empirical methods in its research. The results of this study The legal understanding of the Village community in making land title certificates as well as knowledge about the importance of ownership of land rights certificates is still relatively low, in general, the people who are used as informants do not know about the procedures for making land title certificates. The conclusions in this study confirm that the land is a very basic human need so legal understanding of the community is very urgent to be carried out in managing land certificates, in order to avoid disputes and cases of land grabbing in the community. If viewed from the economic aspect, land certificates can be used by the community to obtain business capital. So that people can improve their standard of living and welfare.